Hemoglobin levels and red blood cell indices in mid‐gestational fetuses with beta‐thalassemia/HbE, beta‐thalassemia trait or Hb E trait and normal fetuses. (4th October 2013) - Srisupundit, Kasemsri; Wanapirak, Chanane; Sirichotiyakul, Supatra; Tongprasert, Fuanglada; Leuwan, Suchaya; Traisrisilp, Kuntharee; Tongsong, Theera
ABSTRACT Objective To compare red blood cell indices among normal, beta‐thalassemia trait or hemoglobin (Hb) E trait, and beta‐thalassemia/Hb E diseases mid‐gestational fetuses. Methods One hundred seventy‐five fetuses at risk of beta‐thalassemia/Hb E disease undergoing cordocentesis with determination of Hb levels and red blood cell indices at mid‐pregnancy were recruited. The fetal diagnoses were based on fetal Hb typing and DNA analysis. The fetuses were divided into three groups: normal, beta‐thalassemia trait or Hb E trait, and beta‐thalassemia/Hb E disease. Results The prevalence of beta‐thalassemia/Hb E disease, beta‐thalassemia trait or Hb E trait, and normal fetuses was 32.6% (57 cases), 28.6% (50 cases) and 36.6% (64 cases), respectively. Mean Hb levels and red blood cell indices were not significantly different among the three groups of fetuses. However, almost 10% of beta‐thalassemia/Hb E fetuses had some degree of anemia. The most anemic fetuses had a β0 mutation. Conclusion There is no significant difference in Hb level and red blood cell indices among fetuses at risk of beta‐thalassemia/Hb E disease. © 2013 John Wiley & Sons, Ltd.